Building & Consolidating the Law Associate Deans (T&L) Network. - Galloway, Kate (Office for Learning and Teaching, 2014)
The purpose of the Law AD Network, comprised of the Associate Deans (Teaching and Learning) (or equivalent) of Australian Law Schools, is to promote collaborative approaches to teaching and learning in Australian legal education. The network intends to lead, encourage and document good practice in learning and teaching in the discipline of law and to create processes and strategies to sustain the network as a sub-Committee of the Council of Australian Law Deans (CALD). Final Summary: A comprehensive national network of Associate Deans Learning and Teaching in Law has produced a set of Good Practice Guides for legal educators and brought Associate Deans together in regular thematic meetings to discuss key issues. Now well-established, the network intends to commence collaborative research and ongoing regular collaboration through network meetings.